TNF-alpha but not IL-1alpha are Correlated with PGE1-Dependent Protection Against Acute D-Galactosamine-Induced Liver Injury - J Muntané; JL Montero; JM Lozano; A Miranda-Vizuete; M de la Mata; G Miño (Canadian Journal of Gastroenterology)
BACKGROUND: Prostaglandin E1 (PGE1) treatment of humans and rodents during acute hepatic failure ameliorates different parameters of hepatic dysfunction.